Mortality, morbidity and medical resources utilization of patients with schizophrenia: A case-control community-based study. (February 2018) - Gur, Shay; Weizman, Shira; Stubbs, Brendon; Matalon, Andre; Meyerovitch, Joseph; Hermesh, Haggai; Krivoy, Amir
Abstract: Patients with schizophrenia have higher level of mortality and physical comorbidity compared to control population. However the association to primary-, secondary- and tertiary-medical resources utilization is not clear. We used a retrospective community-based cohort of patients with schizophrenia ( n =1389; age 37.53 years, 64.3% males) and, age-, gender-, and socioeconomic status-matched controls ( n =4095; age 37.34 years; 64.3% males) who were followed-up for nine years. Mortality rate of patients was almost twice as high as that of matched controls (7% versus 3.8%). Diagnoses of ischemic heart disease and hypertension were more prevalent among controls than patients (8.2% versus 5%, and 21.6% versus 15.8%, respectively). Tertiary medical resources utilization was higher among patients with schizophrenia than control population (mean hospital admissions per year: 0.2 versus 0.12, emergency department visits: 0.48 versus 0.36). Patients that died were more likely to have cardiovascular disease, to be admitted to general hospital and to spend more days in hospital than patients that did not die. There is a discrepancy between lower rates of cardiovascular disease diagnoses but higher rates of mortality and tertiary medical resources utilization among patients with schizophrenia when compared to control population. This may stem from an under-diagnosis and, eventually, under-treatment of these patients. Highlights: Patients with schizophrenia have higher mortality rates than matched controls. However, rates of cardiovascular diagnoses is lower in schizophrenia patients. Schizophrenia patients use more tertiary level medical services. This discrepancy may stem from an under-diagnosis of these patients.